2020
DOI: 10.1007/s12011-020-02139-2
|View full text |Cite
|
Sign up to set email alerts
|

Nano-selenium Supplementation Increases Selenoprotein (Sel) Gene Expression Profiles and Milk Selenium Concentration in Lactating Dairy Cows

Abstract: Supplementation with selenium is common for dairy cows, but the importance of selenium source is not clear. This study aimed to compare nano-selenium (Nano-Se) and sodium selenite supplements for dairy cows on lactation performance, milk Se levels and selenoprotein (Sel) gene expression. Twelve multiparous Holstein cows were randomly divided into two groups: a control group fed a basal diet plus 0.30 mg Se/kg of DM as sodium selenite or Nano-Se for 30 days. Dry matter intake, milk yield and composition were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Many minerals are used as nanoparticles in animal research. These include aluminium (Li et al 2011 ), calcium (Matuszewski et al 2020a ; Abdelnour et al 2021 ; Abo El-Maaty et al 2021 ), copper (Gonzales-Eguia et al 2009 ; Miroshnikov et al 2015 ; Mroczek-Sosnowska et al 2014 , 2015a , 2015b , 2017 ; Refaie et al 2015 ; Joshua et al 2016 ; Ognik et al 2016b ; Scott et al 2016 ; El Basuini et al 2017 ; Tomaszewska et al 2017 ; Scott et al 2018 ; Aminullah et al 2021 ; Morsy et al 2021 ; Naz et al 2021 ), gold (Sembratowicz et al 2016 ; Sanati et al 2019 ; Hassanen et al 2020 ), iron (Pilaquinga et al 2021 ), magnesium (Kesmati et al 2016 ; Mazaheri et al 2019 ; Abdelnour et al 2021 ), nickel (Gong et al 2016 ), selenium (Zhang et al 2001 , 2008 ; Shi et al 2011a ; Wu et al 2011 ; Sadeghian et al 2012 ; Xun et al 2012 ; El-Deep et al 2016 ; Joshua et al 2016 ; Muralisankar et al 2016 ; Yaghmaie et al 2017 ; Gangadoo et al 2018 , 2020 ; Hassan et al 2020 ; Kojouri et al 2020 ; Nabi et al 2020 ; Sheiha et al 2020 ; Han et al 2021 ; Rana, 2021 ), silver (Grodzik and Sawosz 2006 ; Sawosz et al 2007 ; Fondevila et al 2009 ; Fondevila, 2010 ; Ahmadi and Rahimi 2011 ; Pineda et al 2012 ; Kout-Elkloub et al 2015 ; Ognik et al 2016a ; Conine and Frost…”
Section: Production Of Nanoparticles For Animal Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Many minerals are used as nanoparticles in animal research. These include aluminium (Li et al 2011 ), calcium (Matuszewski et al 2020a ; Abdelnour et al 2021 ; Abo El-Maaty et al 2021 ), copper (Gonzales-Eguia et al 2009 ; Miroshnikov et al 2015 ; Mroczek-Sosnowska et al 2014 , 2015a , 2015b , 2017 ; Refaie et al 2015 ; Joshua et al 2016 ; Ognik et al 2016b ; Scott et al 2016 ; El Basuini et al 2017 ; Tomaszewska et al 2017 ; Scott et al 2018 ; Aminullah et al 2021 ; Morsy et al 2021 ; Naz et al 2021 ), gold (Sembratowicz et al 2016 ; Sanati et al 2019 ; Hassanen et al 2020 ), iron (Pilaquinga et al 2021 ), magnesium (Kesmati et al 2016 ; Mazaheri et al 2019 ; Abdelnour et al 2021 ), nickel (Gong et al 2016 ), selenium (Zhang et al 2001 , 2008 ; Shi et al 2011a ; Wu et al 2011 ; Sadeghian et al 2012 ; Xun et al 2012 ; El-Deep et al 2016 ; Joshua et al 2016 ; Muralisankar et al 2016 ; Yaghmaie et al 2017 ; Gangadoo et al 2018 , 2020 ; Hassan et al 2020 ; Kojouri et al 2020 ; Nabi et al 2020 ; Sheiha et al 2020 ; Han et al 2021 ; Rana, 2021 ), silver (Grodzik and Sawosz 2006 ; Sawosz et al 2007 ; Fondevila et al 2009 ; Fondevila, 2010 ; Ahmadi and Rahimi 2011 ; Pineda et al 2012 ; Kout-Elkloub et al 2015 ; Ognik et al 2016a ; Conine and Frost…”
Section: Production Of Nanoparticles For Animal Researchmentioning
confidence: 99%
“…A wide range of nanoparticles, which could be used in animal studies, is accessible on the market as shown in numerous publications, for example Ag (Grodzik and Sawosz 2006 ; Pineda et al 2012 ), Au (Sembratowicz et al 2016 ), Cu (Mroczek-Sosnowska et al 2015b ; Mroczek-Sosnowska et al 2017 ; Aminullah et al 2021 ), Se (Shi et al 2011a ; Xun et al 2012 ; Yaghmaie et al 2017 ; Han et al 2021 ), and Zn (Olgun and Yildiz, 2017 ; Abdollahi et al 2020 ; Cui et al 2021 ; Eskandani et al 2021 ; Szuba-Trznadel et al 2021 ; El-Maddawy et al 2022 ). In many experiments on animals and poultry, nanoparticles were purchased to check their impact on performance, productivity, health, and disease prevention and control.…”
Section: Production Of Nanoparticles For Animal Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthropogenic processes manufacture incidental nanomaterials as side-products [90], while engineered nanomaterials with unique properties are intentionally developed [91]. There is a review of air, water, and soil exposure from different paths.…”
Section: Impact On the Environment And Toxicity Of Nanomineralsmentioning
confidence: 99%